Studi Banding tentang pengembangan vaksin untuk COVID-19 - Alsayed, Raghda; Zainulabdeen, Khalid; Salman, Israa; Hairunisa, Nany; Amalia, Husnun; Yusop, Rahimi M; Redwan, Amamer M; Yousif, Emad (Fakultas Kedokteran Universitas Trisakti, 2023)
The human respiratory system can be infected with coronaviruses (CoVs), one of the families of viruses that can lead to symptoms ranging from mild to fatal. Seven genera of CVS have been identified as having human infection to date. The virus can spread as fine, liquid particles from the mouth or nose of an infected person when coughing, sneezing, speaking, or breathing. The diameter of droplet particles ranges from large to small. In this review, we summarize vaccine development for COVID-19. We anticipate this study will be a valuable resource for any researcher interested in creating a COVID-19 vaccine.